Changes in lysosomal enzymes and mannose-6-phosphate receptors related to sexual maturation in bull epididymis - Aguilera, Andrea Carolina (2015)
One of the most striking features of the mammalian epididymis is the secretion of lysosomal enzymes (LE). These LE may play a role in sperm maturation. In the present study we investigated the activity and distribution of four LE (b-galactosidase (b-Gal), N-acetyl-b-D-glucosaminidase (b-NAG), a-mannosidase (a-Man) and b-glucuronidase) in bull epididymis at two different ages (6 months and 4 years) to determine whether these enzymes vary with sexual 5 maturity. In young, sexually immature (SI) bulls we found high LE activity in the epididymal tissue that accounts for a developed and active lysosomal apparatus. In contrast, low LE activity was measured in sexually mature (SM) bulls, and b-NAG and b-Gal were mostly secreted into the lumen. We also attempted to correlate LE distribution with the expression and functionality of mannose-6-phosphate receptors (MPRs), which are thought to be involved in proper delivery of LE to lysosomes. The cation-dependent MPR was highly expressed in SI bulls, with expression decreasing during adulthood, 10 whereas the expression of the cation-independent MPR was higher in SM than SI bulls. In addition, the four enzymes recovered from the epididymal lumen interact with both MPRs at each age. We conclude that the activity and distribution of LE in bull epididymis varies with sexual maturity and that the distribution is regulated differently by the two types of MPR. These findings could provide some molecular basis for male infertility.